Lock-in thermal laser stimulation for non-destructive failure localization in 3-D devices. (September 2017) - Jacobs, K.J.P.; Wang, T.; Stucchi, M.; Gonzalez, M.; Croes, K.; De Wolf, I.; Beyne, E.
Abstract: We report a new non-destructive method to localize interconnection failures in 3-D devices. The scanning optical microscopy (SOM) technique is based on lock-in thermal laser stimulation (LI-TLS) and uses thermal waves to non-destructively map the current path in a 3-D device. We validate the method with test structures and show how the magnitude and phase of a propagating thermal wave may provide valuable 3-dimensional information on the failure location. We apply the technique on a short failed chain structure in a four level chip stack with an intensity modulated laser as a thermal wave injector and the structure under test as a detector. We confirm our results by physical failure analysis through a selective cross sectioning process. Highlights: We report the application of lock-in thermal laser stimulation for non-destructive fault isolation in 3-D devices. Thermal waves are injected by a laser and subsequently detected by the actual structure under test. The amplitude and phase lag of the thermal wave provide XYZ failure localization. Method is successfully demonstrated on test structures and a short failed 3-D chip stack. Results are confirmed by a selective cross sectioning process.